Internet connectivity disruption in Kenya (Kenya) - Voidly (2026)
CRITICAL severity disruption detected in Kenya. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: KE-2026-0015
Keywords: internet disruption; KE; disruption; critical